Ameliorative Effect of Zinc on Bone Cells of Humerus and Femur of Female Rats Under High Salt Diet - Kaukab Anjum , Hafsa Nisar , SumairaAbbasi , (Journal of Rawalpindi Medical College, 2016)
Background:To evaluate the effect of zinc on bone cells of humerus and femur of female adult Sprague Dawley rats under high salt diet. Methods: In this experimental study 10-12 weeks old,45 adult female Sprague Dawley rats were used. Three groups were made, each having fifteen rats. Control group C received laboratory diet without any alteration. Experimental group A was served with high salt diet (8%NaCl)whereas experimental group B animals were given high salt diet augmented with zinc (50mg/kg/day).All groups were given the diet for eight weeks after which they were sacrificed and left humeri and femora of all rats were obtained.After decalcification, Bone tissue from proximal part of shaft was attained to study the number of osteoblast (bone forming) and osteoclast (bone resorbing) cells.For light microscopy, tissue processing was done to obtain five micrometer (μm) sections. Tissues were stained with Haematoxylin and eosin (H&E).The results were compiled and compared. Results: After salt administration, group Animals showed marked increase in osteoclast number whereas the osteoblast number exhibited substantial decrease. Protective effects were seen in zinc supplemented experimental group B with decrease in osteoclast number and increase in osteoblast number. Conclusion:Zinc has protective effect against high salt induced damage in the bone cells of rats